Probable paralytic rabies in a dog: ante-mortem clinical diagnosis implications in limited resource settings - Viswanathan, Naveenkumar; Sethuraman, Sasikumar; Rajasekaran, Ranjani; Ramalingam, Uma R; Pitchai Navlon, Richard J (The Journal of Infection in Developing Countries, 2024)
Introduction: Rabies is a dreadful zoonotic viral disease that affects animals and humans with a fatality rate of 100%. This report aims to create awareness among the veterinarians and general public about the paralytic form of rabies in order to understand the antemortem clinical diagnosis implications in limited resource settings, so as to follow the post-exposure prophylaxis at the golden hour period of rabies transmission. Case presentation: A one-year-old female dog was presented to the Ambulatory Clinic Unit, Veterinary Clinical Complex, Veterinary College and Research Institute, Theni, Tamil Nadu, India with the ailment of a dropped jaw and was unable to swallow food and water for the past three days. Epidemiological investigations revealed that the animal had dog-bitten wounds from a week ago. On clinical examination, facial distortion, changes in the vocal cord, and paralysis of the throat muscle were noticed. Based on the anamnesis, clinical, and epidemiological investigations, the animal was diagnosed to be a probable case of paralytic form of canine rabies. In the limited resource settings, antemortem clinical diagnosis was practiced to suspect rabies-infected dogs. Further, the owner was advised to implement preventive measures to safeguard against rabies infection. The dog was kept under isolation and succumbed on day two with evidence of progressive paralytic signs. Conclusions: This report emphasizes the importance of paralytic rabies, alongside of furious form of rabies, further creating awareness among the general public about the antemortem clinical diagnosis under limited resource settings.